850Description of total population hospital admissions for Craniosynostosis in Australia. (2nd September 2021) - Junaid, Mohammed; Slack-Smith, Linda; Leonard, Helen; Wong, Kingsley
Abstract: Background: Craniosysnostosis (CS) is a condition ensuing from premature fusion of cranial sutures, resulting in altered craniofacial morphology, requiring early neurosurgical interventions to improve prognosis and outcomes. This study aimed to describe total population hospital admissions related to craniosynostosis in Australia over a 22-year period. Methods: Population summary data for admissions to public and private hospitals were obtained from the Australian Institute of Health and Welfare National Hospital Morbidity Database (July 1996 to June 2018). The primary outcome variable was a hospital separation with the principal diagnosis of craniosynostosis, craniodysostosis or acrocephalosyndactyly (ICD9CM diagnosis codes 756.00 and 756.01 between July 1996– June 1998 and ICD10AM diagnosis codes Q75.0, Q75.1 and Q87.02 for July 1998 onwards). Trends in rates of hospital admission and length of stay by age, gender and type of craniosynostosis were investigated by negative binomial regression. Results: A total of 8, 115 admissions were identified between July 1996 to June 2018. Marginal decrease in hospital admission rates [-0.02 (95%CI 0.03, 0.001)] has been observed over a duration of 22 years. Admissions were higher for males, infants (<1 year) and nonsyndromic cases of disease. Average length of stay at hospitals for CS was calculated to be 5.3 ± 1.3 days per year which were even lengthier with syndromic conditions. Conclusion: This study has identified population level trends in hospital separation for craniosynostosis in Australia. Key Message: Population administrative data, despite limitations provides useful information to inform research and practice.